De-politicising and re-politicising transport infrastructure futures. (November 2022) - Legacy, Crystal
The planning for future transport and its infrastructure is deeply political. Yet, how we understand re-politicisation, and what those efforts tell us about what is political in the planning for future cities, remains under explored. One lens through which to explore these acts is to consider the role of urban coalitions in drawing attention to the dominant politics of planning and setting the ground for the re-politicisation of transport infrastructure futures. Drawing on the work of post-foundational scholars Mouffe and Rancière, this paper examines the interplay between de-politicisation and re-politicisation and how two urban coalitions negotiated this landscape in the Greater Toronto and Hamilton Area during a sustained period of contestation surrounding the proposal of new transport infrastructure. Through this analysis, this paper draws on in-depth interviews with coalition members, transport planners, politicians and engaged citizens to illustrate how these urban coalitions produced a 'collective will' and a struggle towards a 'consensus cure' in their re-politicising actions. This paper reveals how coalition-led re-politicisation establishes the grounds for the politics to shift on contested future transport proposals and offers insight into the incremental and oftentimes incomplete ways re-politicisation nurtures transformational change.